The Role of Managerial Ownership of The Factors That Affect Firm Value in Banking Companies in Indonesia - Sheila Gracia; Hendro Lukman (Graduate Program of Universitas Tarumanagara, 2023)
Objective of this research to prove the effect of intellectual capital, capital structure, and firm growth on firm value. In addition, to see the role of ownership of managerial in moderating the effect of these variables. This is a quantitative research of data obtained from the Indonesia Stock Exchange (IDX). This study’s population are banking companies listed on the IDX during 2016-2020. The technique of sampling used in this study is purposive sampling which resulted 76 observation data during the 2016-2020 period. The data that has been collected will be analyzed using multiple linear regression analysis. The program used in analyzing the data is Statistical Package for the Social Sciences (SPSS) ver. 26. The results obtained in this study are intellectual capital, capital structure, and firm growth simultaneously have an effect on firm value. Partially, intellectual capital and capital structure have no significant effect on firm value, while firm growth has a significant effect on firm value. In addition, managerial ownership is not able to moderate the effect of intellectual capital, capital structure, and firm growth on firm value. The implication of this study is that managerial ownership needs to be considered in terms of achieving common goals in ordering to increase firm value.